A manual for writers of term papers, theses, and dissertations / Kate L Turabian - Turabian, Kate L
"For nearly sixty years Kate L. Turabian's Manual for writers has offered comprehensive and detailed guidance to writers of research papers--term papers, theses, and dissertations. Now the editors of The Chicago manual of style have revised Turabian's Manual to bring the details of style into conformity with the fourteenth edition of the Chicago manual. This new edition of 'Turabian' reflects the way students work today, taking into account the role of personal computers in the preparation and presentation of their papers. This new edition includes information on the components of a long formal paper; the mechanics of writing style, from abbreviations to quotations; how to prepare and refer to tables and illustrations; the most commonly used systems of citation, including how to cite electronic documents; manuscript preparation and hints on word processing software; formatting some of the complex features found in many research papers, including over two dozen sample pages"--Provided by publisher.